Prevention of sudden death in adolescent athletes: Incremental diagnostic value and cost-effectiveness of diagnostic tests. (29th August 2020) - Grazioli, Gonzalo; Sanz de la Garza, Maria; Vidal, Barbara; Montserrat, Silvia; Sarquella-Brugada, Georgia; Pi, Ramon; Til, Lluis; Gutierrez, Josep; Brugada, Josep; Sitges, Marta
Abstract: Introduction: Pre-participation screening in athletes attempts to reduce the incidence of sudden death during sports by identifying susceptible individuals. The objective of this study was to evaluate the diagnostic capacity of the different pre-participation screening points in adolescent athletes and the cost effectiveness of the programme. Methods: Athletes were studied between 12–18 years old. Pre-participation screening included the American Heart Association questionnaire, electrocardiogram, echocardiogram, and stress test. The cost of test was established by the Catalan public health system. Results: Of 1650 athletes included, 57% were men and mean age was 15.09 ± 1.82 years. Positive findings were identified as follows: in American Heart Association questionnaire 5.09% of subjects, in electrocardiogram 3.78%, in echocardiogram 4.96%, and in exercise test 1.75%. Six athletes (0.36%) were disqualified from participation and 10 (0.60%) were referred for interventional treatment. Diagnostic capacity was assessed by the area under the curve for detection of diseases that motivated disqualification for sport practice (American Heart Association questionnaire, 0.55; electrocardiogram, 0.72; echocardiogram, 0.88; stress test, 0.57). The cost for each athlete disqualified from the sport for a disease causing sudden death was €45, 578. Conclusion: The electrocardiogram and echocardiogram were the most useful studies to detect athletes susceptible to sudden death, and the stress test best diagnosed arrhythmias with specific treatment. In our country, pre-participatory screening was cost effective to detect athletes who might experience sudden death in sports.